(untitled) (Bangladesh Pharmaceutical Journal, 2025)
A simple and cost-effective UV spectrophotometric method was developed and validated for the routine analysis of molnupiravir (MLP) using 10% (v/v) methanol as the solvent. The absorption maximum (λmax) of molnupiravir was determined to be 238 nm. The method was validated according to ICH guidelines, and the results demonstrated its suitability, specificity, linearity, accuracy, precision, sensitivity, ruggedness, and robustness. The method showed a linear response within the concentration range of 2-20 µg/ml, with a correlation coefficient (R²) of 0.9972. The accuracy, expressed as % recovery, ranged from 95.92% to 104.38%, while intra-day and inter-day precision studies yielded %RSD values within acceptable limits. The limits of detection (LOD) and quantification (LOQ) were found to be 2.42 µg/ml and 7.34 µg/ml, respectively. Ruggedness and robustness studies further confirmed the reliability of the method under varied conditions. Equivalency studies comparing the developed UV method with a reference RP-UHPLC method demonstrated comparable performance in terms of linearity, accuracy, precision, ruggedness and robustness, with statistical analysis supporting the equivalence of the two methods. The developed UV method offers a viable alternative for the routine analysis of molnupiravir, providing a balance between accuracy and simplicity. Bangladesh Pharmaceutical Journal 28(1): 83-93, 2025 (January)